2022
DOI: 10.1039/d2ob00131d
|View full text |Cite
|
Sign up to set email alerts
|

ROESY and 13C NMR to distinguish between d- and l-rhamnose in the α-d-Manp-(1 → 4)-β-Rhap-(1 → 3) repeating motif

Abstract: Many children suffering from autism spectrum disorder (ASD) experience gastrointestinal (GI) conditions. Enterocloster bolteae has been regularly detected in the stool of individuals suffering from GI symptoms and autism. Literature...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…Another group we noticed is the genera Enterocloster which had a stepped growth of abundance in groups of health, IBS without-and with psychiatric disorders. Enterocloster has been reported to increase in individuals suffering from GI symptoms and autism [29]. Interestingly, we observed that Enterocloster was also signi cantly enriched in IBS-D patients compared with IBS-C and healthy controls.…”
Section: Discussionsupporting
confidence: 46%
“…Another group we noticed is the genera Enterocloster which had a stepped growth of abundance in groups of health, IBS without-and with psychiatric disorders. Enterocloster has been reported to increase in individuals suffering from GI symptoms and autism [29]. Interestingly, we observed that Enterocloster was also signi cantly enriched in IBS-D patients compared with IBS-C and healthy controls.…”
Section: Discussionsupporting
confidence: 46%
“…In some cases, when the absolute configuration of a specific monosaccharide residue of a glycan is known, the absolute configuration of the directly attached monosaccharides can be established through the analysis of 13 C NMR glycosylation shifts. , Interestingly, this strategy has proven useful to assign the absolute configuration of Rha residues linked to a structurally conserved N-glycan moiety of the major capsid protein of some chloroviruses. Depending on the virus species, the rhamnose residue that is linked to O3 of a trisubstituted l -Fuc p residue can have the d- or l -configuration; as predicted, a larger glycosylation shift (displacement) is observed for C1 of the d -Rha residue when compared to that of l -Rha .…”
Section: Identification Of Structural Partsmentioning
confidence: 99%